E-Marketplace as a Tool for the Revitalization of Portuguese Craft Industry: The Design Process in the Development of an Online Platform - Nuno Martins (Future Internet, 2020)
The craft trade in Portugal faces challenges that compromise its productive and economic sustainability and may result in the disappearance of millenary techniques, traditions, and industrial practices of high symbolic and historical value. The growing incompatibility of these traditional activities with digital technologies, the lack of resources, and a growing age gap are among the main problems identified. This situation made worse by various restrictions pertaining to the COVID-19 pandemic points towards the possibility of extinction of this type of manual arts. The goal of this research is to demonstrate how the design process of an e-marketplace platform, throughout its different phases, may contribute to the revitalization of traditional industries. The methodologies adopted in the framework consisted in the study of UX and UI best design practices, including wireframe design, user flows, definition of personas, development of prototypes, and style guides. The results of the conducted usability tests to the prototype allowed a gradual improvement of the solution, culminating in the confirmation of its effectiveness. The study concluded that digital technology, namely a designed e-marketplace solution, could potentially bring buyers and sellers closer together, thus being a tool with high potential for the dissemination and sustainability of the craft industry.